Location and Extent of A1, A2 Release and Its Impact on Tendon Subluxation and Bowstringing—A Cadaveric Study - Bhandari, Laxminarayan; Hamidian Jahromi, Alireza; Miller, Aden Gunnar; Tien, Huey (Indian Journal of Plastic Surgery, 2019)
Surgical treatment of trigger finger involves release of A1 pulley. Some authors have theorized that the loss of A1 pulley can lead to ulnar subluxation of flexor tendons, which can be prevented by release of A1 pulley radially, even in a nonrheumatoid hand. However, there is no evidence in literature to either support or oppose this hypothesis. Occasionally, difficulty is encountered to precisely identify where A1 ends and A2 begins. While incomplete release of A1 can cause relapse of triggering, release of substantial A2 can cause bowstringing. Knowledge of the safe limit of concomitant A2 release is beneficial. The study was conducted in 12 cadaver upper extremity specimens. A1 pulleys of 48 fingers were divided at the radial (24 fingers) or ulnar (24 fingers) attachment. A 20lb traction force was applied on the flexor tendons. Any subluxation or bowstringing was noted. The experiment was repeated following serial release of the A2—initially 25%, followed by 50% and 100%. No bowstringing or subluxation was noted when A1 pulley was opened, either by radial or ulnar incision. The same was true for A1 + 25% A2 release. When A1 + 50% A2 pulley were released, bowstringing was observed in 3/48 fingers. When A1 + 100% of the A2 pulley were released, bowstringing occurred in all cases. The location of incision for release of the A1 pulley has no effect on bowstringing or tendon subluxation. Release of additional 25% of the A2 pulley can be performed safely, which corresponds to the level of palmar digital crease.
Keywords: trigger finger; A1 pulley; A2 pulley; tendon subluxation; complication